Antibacterial Activity of Jeruk Sambal (Citrus microcarpa Bunge) Peel Extract againts Growth Propionibacterium acnes and Pseudomonas aeruginosa - Oktaviani, Khaerunnisa Nur Eka Dyah; Wardoyo, Elvi Rusmiyanto Pancaning; Khotimah, Siti (LenteraBio : Berkala Ilmiah Biologi, 2023)
Propionibacterium acnes and Pseudomonas aeruginosa are examples of bacteria that cause infection in humans skin. Handling skin infections can be done by utilizing the antibacterial content of plants parts, such as jeruk sambal peel waste (Citrus microcarpa Bunge). The point of the inquire about was to see the movement of the antibacterial substance and to discover out the most excellent extricate concentration from orange peel in restraining the development of P. acnes and P. aeruginosa. This think about utilized an exploratory plan with circle dissemination strategy, which included seven distinctive medicines. The medications included extricate concentrations of 10%, 20%, 30%, 40%, tetracycline anti-microbials and ciprofloxacin as positive controls and 10% DMSO as negative controls. The comes about of the consider demonstrated that all concentrations of the orange peel extricate had a critical impact on hindering the development of the tried bacteria. The concentration of 30% extricate was the leading concentration in restraining the development of P. acnes for 48 hours with an hindrance zone of 8,850 mm and was categorized as direct hindrance. The concentration of 20% extricate was the leading concentration in restraining the development of P. aeruginosa for 48 hours with an hindrance zone of 12.325 mm and was categorized as a solid inhibitor.